Organizing MIND Program Development, Implementation and Evaluation at MAP Retail Academy - Katherine Febelia Chandra; Denta Felli Ananda; RR. Niken Purbasari; Maris Agung Triandewo (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This internship report is intended to explain the author's activities during the internship at MAP Retail Academy through the Independent Campus Certified Internship Program organized by the Ministry of Education. This report will explain the author's daily activities as part of the HR Training Intern. This internship report contains the author's activities as a trainer in the Academic division at MAP Retail Academy. In addition to the daily activities regarding the work given, this report will also explain non routine activities provided by MAP Retail Academy and projects outside of the author's daily activities. This program has been running effectively and efficiently in training apprentices to be able to apply learned knowledge, skills, and attitudes such as effective communication, time management, and project management into work related to training.